2012
DOI: 10.1152/ajplung.00049.2012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gut- and lung-derived serotonin attenuates pulmonary hypertension in mice

Abstract: Decreasing the bioavailability of serotonin (5-HT) by inhibiting its biosynthesis may represent a useful adjunctive treatment of pulmonary hypertension (PH). We assessed this hypothesis using LP533401, which inhibits the rate-limiting enzyme tryptophan hydroxylase 1 (Tph1) expressed in the gut and lung, without inhibiting Tph2 expressed in neurons. Mice treated repeatedly with LP533401 (30-250 mg/kg per day) exhibited marked 5-HT content reductions in the gut, lungs, and blood, but not in the brain. After a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 32 publications
(34 reference statements)
3
29
0
Order By: Relevance
“…However, the hypothesized inhibition of lung TPH1 by LP533401 was based on lung measures containing 5-HT-devoid platelets. In addition, the surprising lack of pathway activation within the chronic hypoxia model used questions the validity of serotonin pathway involvement / analytics (Abid et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…However, the hypothesized inhibition of lung TPH1 by LP533401 was based on lung measures containing 5-HT-devoid platelets. In addition, the surprising lack of pathway activation within the chronic hypoxia model used questions the validity of serotonin pathway involvement / analytics (Abid et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The serotoninergic transmission has a broad spectrum of effects and has been associated to neural development [6], numerous behavioral and mood disorders [7-11] and to central modulation of pain [12]. Serotonin, however, can also be synthesized by heterochromaffin cells in the gut, where it regulates gastrointestinal function [13], by endothelial cells in the lung [14] and can be found sequestered inside platelet granules [15,16]. As serotonin cannot cross the hematoencephalic barrier, it forms two physically and functionally separated pools, the former inside the central nervous system and the latter in the peripheral body.…”
Section: Serotoninmentioning
confidence: 99%
“…In addition, TPH-1 knockout mice are protected from hypoxia-induced pulmonary hypertension (PH) (10,11). We have shown that only female mice develop PH via a serotonin-dependent mechanism-for example, mice overexpressing the serotonin transporter (SERT), calcium-binding protein S100A4/mts1-overexpressing mice, and mice dosed with dexfenfluramine (6,12,13).…”
mentioning
confidence: 99%